Auditoría de comunicación interna a la empresa Blenastor, ubicada en el Valle de los Chillo (la Armenia) y propuesta de un plan de acción para optimizar los procesos comunicativos ya existentes - Guarderas Proaño, Bernardo (2011)
This work is an internal communication audit at BLENASTOR company in the city of Quito, to know the communication status of the company, after obtaining the required information is proceeded to the diagnosis, then move to the development of a plan internal communication to improve existing communication processes. Before performing the audit, it was necessary to perform a bibliographic review of the general concepts of communication, its various tools, for internal audiences, learn more about communication on the audit and plan on making an efficient internal communication. To conduct the audit of internal communications, had to know about the company BLENASTOR first thing we did was to inquire about its history, and how it handles the communication within the company and was also very important work conducted by field visits, meetings with the assistant manager, and the development of surveys of employees working inside the plant which is located in Armenia, valle de los chillos, Quito-Ecuador, trying to get a primary source what is the real situation regarding internal communication BLENASTOR. After obtaining the data required was an assessment of the situation of internal company communication, thus, analyze problems and make a plan for internal communication to improve communication problems detected. In developing the plan were discussed one by one the problems that the company and based on these data, we proposed objectives, strategies and actions with that based on a schedule of activities will be developed for internal communication problems BLENASTOR company, will be overcome.